2021
DOI: 10.1038/s41370-021-00335-3
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal activity in commonly used Black hair care products: evaluating hormone disruption as a plausible contribution to health disparities

Abstract: Background: Certain types of hair products are more commonly used by Black women.Studies show hair products contain several endocrine disrupting chemicals that are associated with adverse health outcomes. As chemical mixtures of endocrine disruptors, hair products may be hormonally active, but this remains unclear.Objective: To assess hormonal activity of commonly used Black hair products. Methods:We identified 6 commonly used hair products (used by >10% of the population) from the Greater New York Hair Produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…A survey of U.S. women found the highest use of hair products among African Americans and African Caribbeans and, according to ingredient labels, their products were more likely to contain endocrine disrupting chemicals (EDCs) [ 24 ]. Six of the products identified from the survey were found to be hormonally active, with some having estrogenic properties, which is of concern for hormone-mediated diseases such as breast cancer [ 25 ]. Helm et al [ 26 ] measured EDCs and asthma-associated chemicals in 18 hair products identified in the same survey and found that many of these chemicals were not disclosed on the product label.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of U.S. women found the highest use of hair products among African Americans and African Caribbeans and, according to ingredient labels, their products were more likely to contain endocrine disrupting chemicals (EDCs) [ 24 ]. Six of the products identified from the survey were found to be hormonally active, with some having estrogenic properties, which is of concern for hormone-mediated diseases such as breast cancer [ 25 ]. Helm et al [ 26 ] measured EDCs and asthma-associated chemicals in 18 hair products identified in the same survey and found that many of these chemicals were not disclosed on the product label.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a survey of 301 African American, African Caribbean, Hispanic, and White women in New York City found that African Americans and African Caribbeans used the largest number of hair products and that 69% of the products used contained endocrine disrupting chemicals (EDCs), including parabens [31]. A study on the hormonal activity of commonly used Black hair products found that all of the examined products had estrogen agonist properties, a concern for health outcomes associated with estrogen disruption [32]. Previous studies have also looked at the prevalence of chemical hair straightening, with one finding that in a cohort of African American women adolescence may be a time of increased usage and potential exposure among African American women [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, women of all races/ethnicities were more likely to use these products compared to men [63]. Together, these studies suggest that the environmental contaminants found in hair products can negatively impact the endocrine system, potentially contributing to racial health disparities and sex-related differences in disease occurrence [59,[62][63][64].…”
Section: Use Of Personal Care Productsmentioning
confidence: 90%